(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores the theoretical foundations of digitizing advocacy activities, focusing on the integration of digital technologies into legal practice. It analyzes the significance of digitization in enhancing the quality of legal services, improving operational efficiency, and strengthening client relationships. The study examines the advantages, challenges, and future prospects of adopting digital tools in advocacy. By reviewing existing literature and real-world applications, the article provides a comprehensive framework for understanding the role of digitization in transforming advocacy. Two tables are included to summarize key digital tools and their impact on advocacy practices.